LAYANAN CYBERCOUNSELING DALAM MENGATASI PROBLEMATIKA PEMBELAJARAN DARING DI MASA DARURAT COVID-19 - Sri Windarti; Alivermana Wiguna (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2020)
Cybercounseling services are considered very suitable for reaching students who need help, because many students experience problems when learning to be brave during the Covid-19 pandemic. The focus of this research is about the problems faced by students during courageous learning, and about cybercounseling carried out by guidance and counseling teachers in an effort to overcome the problems faced by these students. The methodology used in this research is descriptive qualitative, with the research subjects being students of the East Kotawaringin Madrasah Aliyah (MAN), which is referred to as 35 people. The interview method used interview data through the What's App application when counseling was conducted, and data analysis used a qualitative descriptive method. Problems that arise from students during learning during the Covid-19 emergency are quite diverse, starting from internal factors and internal factors. The presence of cybercounseling conducted by guidance and counseling teachers provides valuable meaning for students to facilitate students to be able to make behaviour changes, construct thoughts, develop the ability to cope with life situations during this pandemic, make decisions that affect them, and succeed. learn the learners.